Behold this heart : St. Francis de Sales and devotion to the sacred heart - Dailey, Thomas F. (Manchester Sophia Institute press, 2020)
"Explains the Salesian devotion to the Sacred Heart of Jesus and includes a novena in that tradition"--
Includes bibliographical references (pages 191-197).
Keywords: Francis, -- de Sales, Saint, -- 1567-1622.; Sacred Heart, Devotion to